REINFORCEMENT STRATEGIES EMPLOYED BY THE ENGLISH TEACHERS AT JUNIOR HIGH SCHOOL 17 KOTA JAMBI - Ani Kurniasih; Wahyuni Fitria; Reni Andriani (International Journal of Research on English Teaching and Applied Linguistics, 2022)
Reinforcement is any response both in verbal and non verbal which modift students’ behavior in order to give feedback on their behavior either as a support or correction (Uzer Usman, 2005). This study focuses on investigating the kinds of reinforcement employed by English teacher at Junior High School 17 Kota Jambi class VIII. Researcher used qualitative method. The researcher also took 2 teachers who teaching in VIII class of Junior High School 17 Kota Jambi as the subject of the study. Techniques of collecting the data were interview and observation. In supporting the data was the observation of 2 English teachers. The result of research showed that the teachers gave both of verbal and non-verbal reinforcement during teaching English in class, such as Verbal reinforcement: Word reinforcement and Sentence reinforcement. Also Nonverbal reinforcement: gesture, proximity, activity and token/symbol. It also proved that giving kinds of reinforcement create good athmosphere into the class.